(untitled) - Kolb, Edward W. (Reading, Mass., 1990)
he Early Universe has become the standard reference on forefront topics in cosmology, particularly to the early history of the Universe. Subjects covered include primordial nubleosynthesis, baryogenesis, phases transitions, inflation, dark matter, and galaxy formation, relics such as axions, neutrinos and monopoles, and speculations about the Universe at the Planck time. The book includes more than ninety figures as well as a five-page update discussing recent developments such as the COBE results.
Keywords: Vũ trụ học,Cosmology